Development of Hepatocellular Carcinoma Associated with Anabolic Androgenic Steroid Abuse in a Young Bodybuilder: A Case Report. (5th July 2012) - Hardt, Aline; Stippel, Dirk; Odenthal, Margarete; Hölscher, Arnulf H.; Dienes, Hans-Peter; Drebber, Uta
Abstract : Introduction . Many different etiological factors are involved in the development of hepatocellular carcinoma (HCC). We report the case of HCC in a 37-year-old male professional bodybuilder with extensive anabolic androgenic (AAS) steroid abuse. Case Presentation . Because of increasing epigastric and abdominal pain, abdominal ultrasound was performed in a 37-year-old male professional bodybuilder. A hyperechoic lesion in the liver was detected in segment VI. The magnetic resonance imaging showed hepatomegaly and confirmed the lesion, which showed features of a hepatocellular adenoma (HCA). Laboratory values were inconspicuous. After laparoscopic segmentectomy the histological examination revealed HCC. Conclusion . While the development of HCA in the liver by chronic intake of AAS is well known, little is known about the association with HCC. The presented case may indicate aetiological association of chronic intake of AAS and the development of HCC.